2023
DOI: 10.3390/ani13071237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Dietary Protein Levels on the Growth Performance, Physicochemical Indexes, Quality, and Molecular Expression of Yellow River Carp (Cyprinus carpio haematopterus)

Abstract: A 12-week rearing trial was carried out to estimate effects on the growth performance, physicochemical indexes, quality, and the molecular expression of Yellow River Carp (Cyprinus carpio haematopterus) using five practical diets, including dietary protein levels of 220, 250, 280, 310, and 340 g/kg. The results illustrated that the fish’s weight gain (WG) and specific growth rate (SGR) were significantly influenced, with an ascending dietary protein level of up to 250 g/kg (p < 0.05). The carp muscle conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Additionally, the growth parameters were shown to increase with dietary protein levels up to 35% in another study (Barlaya et al, 2022). However, it is important to note that the relative GH expression of carp muscle significantly decreased with the increasing dietary protein level up to 310g/ kg in the Yellow River Carp study, and then it significantly increased (Wang et al, 2023).…”
Section: T4 (35%) Initialmentioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, the growth parameters were shown to increase with dietary protein levels up to 35% in another study (Barlaya et al, 2022). However, it is important to note that the relative GH expression of carp muscle significantly decreased with the increasing dietary protein level up to 310g/ kg in the Yellow River Carp study, and then it significantly increased (Wang et al, 2023).…”
Section: T4 (35%) Initialmentioning
confidence: 89%
“…DWG, TWG, WGR, RGR, MGR, and SGR were improved after dietary protein levels at a concentration (T2, 28%). A study on the Yellow River Carp demonstrated that the fish's WG and SGR were significantly influenced by the dietary protein level, with an ascending trend up to 250g/ kg (Wang et al, 2023). Another study found that increased dietary protein improved the growth of both growth hormone gene (GH) transgenic and non-transgenic carp (Guo et al, 2021).…”
Section: T4 (35%) Initialmentioning
confidence: 99%